Big Data Analytics in Decision Making: A Bibliometric Mapping of Scientific Contributions - Judijanto, Loso (Westscience Press, 2025)
This study aims to map the intellectual, conceptual, and collaborative landscape of scientific research on Big Data Analytics (BDA) in the context of decision-making using a bibliometric approach. Drawing data from the Scopus database and analyzing it through VOSviewer, the study identifies publication trends, influential authors, high-impact journals, keyword co-occurrence patterns, and international collaboration networks. The results reveal that